Samoa : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Samoa reports that remittances are the main source of foreign exchange to the Samoan economy. In addition to remittances, travel credits also play an important role in the economy. Official transfers are also significant, and should remain an important source of balance-of-payments support over the medium term. Remittances are relatively more stable when measured in the remitting country's currency compared with talas. Remittance receipts account for a similar share of income across different household income groups, except for the richest one.